I am supposed to derive this equation: g=aave(M + m / m) It gives me two pairs of equations: T1-Fr = Ma1 mg-T1= ma1 and T2 + Fr = Ma2 mg - T2 = ma2 It also says, "hint: for the first pair of equations, eliminate the unknown tension. Do the same for the second pair of equations. In this new pair of equations, eliminate the unknown force of kinetic friction Fr. So I tried just canceling out the T in the first set of equations, leaving me with -Fr = Ma1 and mg = ma1, but that doesn't seem right. I am mostly just confused on how to "derive an equation". I'm just looking for a little direction--do I set them equal to each other? I'm just confused on what it's asking, I've never done a problem like this before and have been trying to understand it forever! Any help would be greatly appreciated. Thanks!!